The Impact of Project-Based Learning on English Subject for Third Semester Students of Indonesian Education Study program, Faculty of Teacher Training and Education, University of Borneo, Tarakan - Fitriawati, Fitriawati (Linguistics and ELT Journal, 2023)
The purpose of this study is to determine the impact of student learning outcomes by using Project Based Learning (PjBL) in the Indonesia Education Department at the University of Borneo Tarakan. This research uses descriptive method with qualitative approach. The researcher uses 3 techniques to collect data which include observation, interview, and documentation.  Students must create a project that will be displayed at the end of the lesson. The results of this study show that student learning outcomes in applying PjBL indicated satisfactory results of 77% of the tasks given and integrated in 4 PjBL steps, namely Preparation, Implementation, Development, and Presentation.